2012
DOI: 10.1016/j.ijrobp.2011.09.057
|View full text |Cite
|
Sign up to set email alerts
|

High and Low LET Radiation Differentially Induce Normal Tissue Damage Signals

Abstract: Our results indicate that diverse mechanisms involved in the development of normal tissue damage may be differentially affected by high and low LET radiation. This may have consequences for the development and manifestation of normal tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 33 publications
(60 reference statements)
3
42
0
Order By: Relevance
“…X-rays, gamma rays and charged particles are the most common types of radiation used for cancer treatment. Recent advances in radiotherapy have enabled the use of different types of radiation sources for a better cancer treatment efficacy [27] . Biological effects of IR on cellular molecules can be direct (target effects) and indirect (no target effects) [21,28] .…”
Section: Ir and Its Effects On The Cellmentioning
confidence: 99%
“…X-rays, gamma rays and charged particles are the most common types of radiation used for cancer treatment. Recent advances in radiotherapy have enabled the use of different types of radiation sources for a better cancer treatment efficacy [27] . Biological effects of IR on cellular molecules can be direct (target effects) and indirect (no target effects) [21,28] .…”
Section: Ir and Its Effects On The Cellmentioning
confidence: 99%
“…High LET has the potential to intensely damage regions of the cell membrane and its proteins, theoretically leading to a more robust antigen. Therefore, tumor cells at the edge of the SOBP may experience an enhanced rate of apoptosis due to the high LET that results in a higher ionization density within the cellular structure compared with the lower LET of photon radiation . Thus, we hypothesized that proton therapy may be a better upregulator of RITI compared with conventional photon radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent reports, it has been demonstrated that High LET irradiation increases killing effects on the CSLCs of colorectal (2), pancreatic (7), glioblastoma (6,8), human tongue (9) and breast (10) cells. However, expensive establishment of high LET caused some limitations to access this modality (2,11). Therefore, the improvement of conventional radiotherapy effects by using some strategies such as application of a radiosensitizer can be considered as an effective and affordable method.…”
Section: Introductionmentioning
confidence: 99%